Alternative economic spaces - Leyshon, Andrew; Lee, Roger 1945-.; Williams, Colin C. 1961-. (London SAGE, 2003)
This text focuses on the emergence of alternative economic geographies within developed economies and analyses the emergence of alternative economic practices within industrialized countries.
Includes bibliographical references and index.
Keywords: Economic geography; Social ecology; Human geography; Electronic books